Pengaruh Senam Lansia Terhadap Kadar Asam Urat pada Lansia di Wilayah Kerja Puskesmas Motaha - Hendrayadi, Hendrayadi; Mimiyati, Mimiyati (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
The incidence of gout in 2008 reported by the World Health Organization (WHO) reached 20% of the world's population who had gout, of which 5-10% were those aged 5 - 20 years and 20% were those aged 55. year. The prevalence of uric acid in Indonesia according to the results of a study conducted by Zeng QY et all reached 23.6% to 31.3%. Data obtained from the Motaha Public Health Center for gout disease were 32 people (66.7%) of the number of elderly people suffering from the disease. This study aims to determine the effect of elderly exercise on uric acid levels in the elderly in the working area of ​​Motaha Health Center. This type of research is a quasi-experimental one group pre-post test. The population in this study were 32 people with a total sampling technique of sampling with a total sample of 30 people. The method of analysis used a statistical test Paired sample t-test. The results showed that the uric acid levels before participating in the elderly exercise of 30 respondents had an average uric acid level with a mean value of 9.95 mg/dl and after the elderly exercise the mean value was 7.94 mg/dl. Meanwhile, uric acid levels in the elderly before and after elderly exercise there was a decrease with a mean value of 2,003 and a significance value of less than 5% (p = 0.000 < 0.05), so it can be concluded that there is an effect of elderly exercise on uric acid levels in the elderly in the working area of ​​Motaha Health Center . Based on the results of the study, it can be concluded that elderly exercise is an effort to reduce uric acid levels in the elderly. It is hoped that health service institutions will provide elderly gymnastics activities in order to be able to improve health status, especially the elderly population in their working area